Exploring Lantana camara: A comprehensive insight into its bioactive constituents and therapeutic potential - Kavita Narayan Gaisamudre (Sarwade),; Prakash Pralhad Sarwade,; Kalpana Sonwani,; Subhash Chand,; Rekha Mehta,; Navin Chandra Pant, (Asian Journal of Pharmaceutical Research and Development, 2025)
Lantana camara is a common medicinal shrub that is known to have a wide composition of phytochemicals and has a wide therapeutic scope. The plant has had a traditional significance in treating respiratory disorders, skin ailments, infections, and inflammatory diseases but scientific attention has been given to it because of the existence of bioactive substances, including terpenoids, flavonoids, phenolic acids, glycosides, and essential oils. These elements lead to various pharmacological effects such as anti-inflammatory, antimicrobial, antioxidant, anticancer, analgesic, hepatoprotective and wound-healing and metabolic regulation. The present review summarizes the existing information on the botanical features, traditional applications, phytochemistry, and the biological activities that have been reported on L. camara. It also presents significant shortcomings in the prevailing literature such as phytochemical profile variability, inconsistency in the methodological approach, lantadene toxicity issues, and absence of clinical validation. The next round of research will focus on adoption of standardized extraction techniques, elaborate toxicity testing, chemotype characterization and clinical trials to confirm the therapeutic claims. On the whole, Lantana camara is a promising but under-investigated source of natural compounds that may be applied in the development of modern drugs.